43 Personalised care planning tool for dying patients; peoples perceptions and impact on care. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Tredgett, Kate; Brown, Karen
Abstract : Introduction: In response to 'One chance to get it right' we developed a local tool to support the care of dying people in an acute hospital. It comprised a document with guidance and tear out elements for clinical staff and a patient/family information book. We report on the data acquired on the tool's impact on care and the perceptions of relatives and clinicians. Methods and results: -Impact on care; This was evaluated through feedback from bereaved families using a validated questionnaire. Questionnaire responses were compared for the deaths supported and not supported by the tool. Overall score for quality of care from 123 completed questionnaires was 16% higher when care was supported by the tool (72% v 88%). -Clinician Feedback; More than 75% of Trust staff have completed mandatory video based e.learning training in care of the dying and in using the tool. Feedback was collected from 60 medical and nursing staff of mixed grades following a learning event. 63% rated the tool 'very helpful' with the remainder rating it 'quite helpful'. Comments included that the tool provides 'written evidence of discussions' and 'staff are aware of the patient's wishes, ' and highlighted practical issues including that 'it is necessarily extensive and takes a long time to complete'. -Family Feedback; In addition to the completing the validated questionnaire, families were invited provide feedback on the tool itself. 96% of respondents rated it very or quite helpful with comments including 'discussed in detail' and 'I'm glad it was there'. Discussion: The findings suggest that the tool is helpful. Because deaths not supported by the tool may differ systematically from those supported by the tool, there may be bias which could dilute the tool's impact as evaluated by the questionnaire. Clinician and family feedback support its ongoing use and continued development.